BLOOD HEMOGLOBIN LEVELS OF CROSS PIGS GIVEN IRON SUPPLEMENTS BASED ON DIFFERENCES IN BODY WEIGHT - Kumara, I Dewa Made Upadana; Merdana, I Made; Sulabda, I Nyoman (Buletin Veteriner Udayana; Vol. 15 No. 6 December 2023DO - 10.24843/bulvet.2023.v15.i06.p08, 2023)
Iron deficiency results in piglets experiencing anemia with a clinical lack of red blood cells and low levels of hemoglobin (Hb) in the blood. This study aims to determine hemoglobin levels and differences in blood hemoglobin levels of pre-weaning crossbreed piglets given iron supplementation by injection in the pre-weaning period based on pre-weaning differences. This study used a sample of 36 pre-weaning cross piglets which were divided into two treatments, each with 6 replications for group K0 and 6 replications for group K1. Treatment in the K0 group as a control will be given a placebo in the form of an aquabidest injection, and in the K1 group given iron supplementation at a dose of 200 mg per head on the second day after birth. Blood sampling was carried out three times, namely when newborn, 7 days old, and 28 days old. Furthermore, examination of blood hemoglobin levels, using the EasyTouch GCHb tool. The results showed that iron supplementation in crossbreed piglets could maintain hemoglobin levels in the pre-weaning period.